BULLYING AND SOCIAL EXCLUSION OF STUDENTS WITH HIGH ABILITIES/GIFTEDNESS IN MIDDLE SCHOOL: A CRITICAL ANALYSIS OF SCHOOL INCLUSION STRATEGIES IN LIGHT OF LITERATURE AND PUBLIC POLICIES - Perez, Cíntia Batista Santos; Galasso , Bruno José Betti (Seven Editora, 2025)
This paper discusses the relationship between bullying and social exclusion of students with high abilities/giftedness (HA/G) in Middle School, based on a critical analysis of scientific literature and Brazilian educational public policies. The research, qualitative and exploratory in nature, was based on systematic bibliographic and documentary review, including cientific articles, legal guidelines, and data from the School Census from 2021 to 2024. The results indicate that, despite normative advances, there is a gap between legislation and school practice, especially regarding early identification and adequate support for HA/G students. It is concluded that bullying, combined with the lack of effective inclusion policies, contributes to the invisibility and underutilization of these students' potential. Twice-exceptionality and intersectionality are also discussed as aggravating factors.DOI: https://doi.org/10.56238/sevened2025.038-013